Pediatric Recurrent Vesicular Palmoplantar Dermatitis Presenting with Pyrexia: A Case Report - Khalifa, Nayla Al; Raees, Mazen; Khalifa, Salman Al; Juffairi, Eman Al (Archives of Clinical and Medical Case Reports, 2024)
Background: Recurrent palmoplantar dermatitis is a a subtype of chronic hand eczema, presenting with deep-seated palmoplantar vesicles or bullae. Although demographics of recurrent palmoplantar dermatitis in the pediatric age group is obscure, the disorder was found to commonly affect children. Moreover, no standardized global diagnostic and treatment guidelines have been established yet. Case presentation: In this case report, we present a 5-year-old male patient, known case of nummular dermatitis, presenting with severe palmoplantar bullae and fever. Conclusions: To date, this is the first case presentation demonstrating a possible viral trigger in pediatric recurrent palmoplantar dermatitis. Further large-scale studies can potentially prove such etiology.